(untitled) - Wingo, Ajume H. (Cambridge,New York, 2003)
Ajume H. Wingo argues that non-rational factors--rhetoric, symbols, and traditions--provide the actual source of motivation in the development and sustainability of the liberal democratic state. Drawing from historical and philosophical sources, Wingo demonstrates that these "veils" can play an essential role in a thriving, stable liberal democratic state.
Keywords: Democracy,Political culture,Symbolism in politics,Rhetoric,Dân chủ,Văn hóa chính trị,Biểu tượng trong chính trị; Political aspects